Beneficial plants-Trichoderma interactions on host tolerance to abiotic stresses: a meta-analysis - dos Santos, Lorena Brito Pimentel Rodrigues; Oliveira-Santos, Naiane; Novais, Diogo Pereira Silva de; Cruz-Magalhães, Valter; Loguercio, Leandro Lopes (Frontiers in Plant Physiology, 2025)
Salinity, drought, and heavy metal contamination are abiotic stresses that pose significant challenges to agricultural productivity, compromising growth and development of plants. Strategies based on plants association with beneficial microorganisms, such as species of the Trichoderma genus, have been widely investigated due to their mitigating and protective potential against these adversities. This study aimed to organize and consolidate evidence on the contribution of Trichoderma spp. to plant resistance/tolerance against those three types of abiotic stresses. To achieve this, a series of meta-analysis were conducted on four groups of response variables in plants: growth and development, physiology/photosynthesis, enzymatic activities, and metabolites. Plants under abiotic stress conditions were compared with and without Trichoderma spp. inoculation. The presence of Trichoderma resulted in increased plant biomass, both in aerial and root parts, as well as in enhancement of photosynthesis-related parameters under all stress conditions. Specifically, positive effects were observed in chlorophyll fluorescence (ChlF), stomatal conductance (Gs), chlorophyll a (Chl a), and relative water content (RWC) under salinity stress; in Gs and RWC under drought; and in Chl a and Chl b under heavy metals exposure. Regarding antioxidant and enzymatic activities, we observed (i) increases in catalase (CAT) and total phenols, along with a reduction in malondialdehyde (MDA) and O2- under drought conditions; (ii) increases in ascorbate peroxidase (APx), superoxide dismutase (SOD) and total phenols, with a reduction in O2- and H2O2 under salinity stress; and (iii) increases in APx and SOD in the presence of heavy metals. Metabolite analysis revealed an increase in proline production under salinity stress and a reduction under drought. Taken together, the results highlight that associations with Trichoderma spp. tend to enhance plant adaptation to abiotic stresses by promoting plant growth and development, increasing chlorophyll production, controlling oxidative stress more efficiently by reducing the levels of reactive oxygen species (ROS), and contributing to osmotic balance under salinity conditions. Overall, this study reinforces the potential of Trichoderma spp. as a tool for managing abiotic stress in agriculture, in the context of environmental and climatic changes.